The Effect of Using Bio-Solar Fuel with Additives, Solar Dexlite and Pertamina Dex on Mitsubishi L300 Diesel in 2007 on Vehicle Smoke Density: Pengaruh Penggunaan Bahan Bakar Bio Solar Dengan Zat Aditif, Solar Dexlite dan Pertamina Dex pada Mitsubishi L300 Diesel Tahun 2007 Terhadap Kepekatan Asap Kendaraan - Iqlima, Anita Rahma Nur; Firdaus, Rachmat (Indonesian Journal of Innovation Studies, 2021)
Diesel engined vehicles are one of the biggest causes of air pollution. Exhaust emissions will continue to increase along with the growth in the number of motorized vehicles, especially for commercial vehicles. The main purpose of this study is to determine the quality of fuel can affect the level of smoke density in diesel engines. This research was conducted by testing sampling on a motor vehicle that is commonly used by the public, namely the Mitsubishi L300 in 2007 production using a Smoke Tester. The test mechanism utilizes different fuel variables, namely: Bio Solar with Additive Substances, Solar Dexlite and Pertamina Dex. From the test results, the highest smoke density value was achieved on Bio Solar fuel with additives at 4200 rpm engine speed with a value of 34.1%. Keywords: Vehicles, Diesel Engines, Smoke Density, Fuel Quality, Additives